Association between pretreatment lymphocyte count and efficacy of immune-enhancing therapy in acute necrotising pancreatitis: a post-hoc analysis of the multicentre, randomised, placebo-controlled TRACE trial. (April 2023) - Ke, Lu; Mao, Wenjian; Shao, Fang; Zhou, Jing; Xu, Minyi; Chen, Tao; Liu, Yuxiu; Tong, Zhihui; Windsor, John; Ma, Penglin; Li, Weiqin; ,; et al.
Summary: Background: Immune-enhancing thymosin alpha 1 (Tα1) therapy may reduce infected pancreatic necrosis (IPN) in acute necrotising pancreatitis (ANP). However, the efficacy might be impacted by lymphocyte count due to the pharmacological action of Tα1. In this post-hoc analysis, we tested the hypothesis that pre-treatment absolute lymphocyte count (ALC) determines whether patients with ANP benefit from Tα1 therapy. Methods: A post-hoc analysis of data from a multicentre, double-blind, randomised, placebo-controlled trial testing the efficacy of Tα1 therapy in patients with predicted severe ANP was performed. Patients from 16 hospitals of China were randomised to receive a subcutaneous injection of Tα1 1.6 mg every 12 h for the frst 7 days and 1.6 mg once a day for the following 7 days or a matching placebo during the same period. Patients who discontinued the Tα1 regimen prematurely were excluded. Three subgroup analyses were conducted using the baseline ALC (at randomisation), and the group allocation was maintained as intention-to-treat. The primary outcome was the incidence of IPN 90 days after randomisation. The fitted logistic regression model was applied to identify the range of baseline ALC where Tα1 therapy could exert a maximum effect. The original trial is registered with ClinicalTrials.gov, NCT02473406 . Findings: Between March 18, 2017, and December 10, 2020, a total of 508 patients were randomised in the original trial, and 502 were involved in this analysis, with 248 in the Tα1 group and 254 in the placebo group. Across the three subgroups, there was a uniform trend toward more significant treatment effects in patients with higher baseline ALC. Within the subgroup of patients with baseline ALC≥0.8 × 10ˆ9/L (n = 290), the Tα1 therapy significantly reduced the risk of IPN (covariate adjusted risk difference,  −0.12; 95% CI,  −0.21, -0.02; p = 0.015). Patients with baseline ALC between 0.79 and 2.00 × 10ˆ9/L benefited most from the Tα1 therapy in reducing IPN (n = 263). Interpretation: This post-hoc analysis found that the efficacy of immune-enhancing Tα1 therapy on the incidence of IPN may be associated with pretreatment lymphocyte count in patients with acute necrotising pancreatitis. Funding: National Natural Science Foundation of China .